2014
DOI: 10.1038/ncomms5744
|View full text |Cite
|
Sign up to set email alerts
|

Trans-regulation of oligodendrocyte myelination by neurons through small GTPase Arf6-regulated secretion of fibroblast growth factor-2

Abstract: The small G protein ADP-ribosylation factor 6 (Arf6) plays important roles in a wide variety of membrane dynamics-based cellular events such as neurite outgrowth and spine formation in vitro. However, little is known about physiological function of Arf6 in vivo. Here we generate conditional knockout mice lacking Arf6 in neurons, oligodendrocytes, or both cell lineages, and unexpectedly find that Arf6 expression in neurons, but not in oligodendrocytes, is crucial for oligodendrocyte myelination in the hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…It was also recently reported that neurons contribute to the regulation of oligodendrocyte myelination through the expression of GTPase Arf6, which controls the secretion of FGF-2. In mice with Arf6 knocked out specifically in neurons, secretion of FGF-2 was reduced and myelination was abnormal (Akiyama et al, 2014). …”
Section: Factors Affecting Remyelination After Strokementioning
confidence: 99%
“…It was also recently reported that neurons contribute to the regulation of oligodendrocyte myelination through the expression of GTPase Arf6, which controls the secretion of FGF-2. In mice with Arf6 knocked out specifically in neurons, secretion of FGF-2 was reduced and myelination was abnormal (Akiyama et al, 2014). …”
Section: Factors Affecting Remyelination After Strokementioning
confidence: 99%
“…Arf6 flox/flox mice 26 were crossed with PF4-promoter-driven Cre-recombinase transgenic mice (Dr Radek Skoda, University Hospital, Basel, Switzerland). 27 Each animal was genotyped by polymerase chain reaction using DNA from tail biopsies.…”
Section: Mouse Generation and Genotypingmentioning
confidence: 99%
“…22 In that study, we employed CNP-Cre mice to produce O-Arf6-CKO mice which did not show any abnormality in axon myelination, suggesting that Arf6 in OPCs/oligodendrocytes is dispensable for myelination. Considering that efficiency of Cre-mediated recombination in OPCs is about 50%, 35 however, we cannot totally rule out the possibility that Arf6 expressed in OPCs/oligodendrocytes is also involved in myelination: if Arf6 in OPCs/oligodendrocytes is completely knocked out, defect in axon myelination may be induced.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…1). 22 FGF-2 is secreted through the unconventional secretion pathway in which FGF-2 is directly translocated across the plasma membrane. In this pathway, phosphatidylinositol 4,5-bisphosphate (PI4,5P 2 ) locally synthesized at the plasma membrane directly binds to FGF-2 to trigger its secretion.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%